Prediction of Marital Expectations based on Communication Beliefs and Marital Attitudes in Pre-Marriage Girls - Seyed Kavousi , Sepideh Sadat; Mardookhi , Mohammad Saeed; Moqarreb tourtolash , Mina (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study aimed to predict marital expectations based on communication beliefs and marital attitudes in pre-marriage girls. Methods: The research had a descriptive-correlational design and its statistical population consisted of all pre-marriage female students at Payame Noor University (PNU) in Tehran in 2020. Using the convenience sampling method, 145 pre-marriage girls were selected as the statistical sample and they answered the Communication Beliefs Questionnaire by Idelson and Epstein (1982), the Marital Attitude Scale (MAS) by Braaten and Rosen (1998), and the Marital Expectation Scale by Jones and Nelson (1996). Results: The results of the Pearson correlation coefficient and regression indicated that communication beliefs and all of their components had a significant positive relationship with pessimistic and idealistic marital expectations and a significant negative relationship with realistic marital expectations (p<0.05). Among the marital attitudes, pessimistic and idealistic attitudes had a significant positive relationship with pessimistic and idealistic expectations, and optimistic and realistic attitudes had a significant negative relationship with pessimistic expectations (p <0.05). Optimistic and realistic attitudes had a significant negative relationship with idealistic and realistic marital expectations, and pessimistic and idealistic attitudes had a significant negative relationship with realistic expectations of pre-marriage girls (p<0.05). Communication beliefs and marital attitudes had a 0.83 correlation with pessimistic marital expectations of pre-marriage girls, in other words, 69% of changes in pessimistic expectations of pre-marriage girls were explained by a linear combination of communication beliefs and marital attitudes. Conclusion: Given the roles of communication beliefs and marital attitudes in marital expectations, psychologists and counselors can take them into consideration in premarital counseling.